UI/UX Design of Mobile-Based Employee Attendance Information System Using Design Thinking Methodology - Kisnanda, M. Farhan; Rizki Abi Awalia, Fadillah; Laple Satria Putra, Rani (Bahasa Indonesia, 2023)
Attendance is a data collection process aimed at obtaining information about the presence or absence of an employee within a company. However, many companies still manually handle the employee attendance process, leading to several issues such as poorly managed attendance data, lack of supervision over employee work hours, and difficulty in updating employee data. Addressing these challenges, there is a need for the design of a User Interface/User Experience (UI/UX) for an Employee Attendance Information System to provide a conceptual framework that can be implemented in the future. The research methodology employed is the Design Thinking method, involving five stages: Empathize, Define, Ideate, Prototype, and Testing. The research findings encompass the design appearance of each page in the application, along with design testing using Usability Testing. The results indicate a high level of satisfaction with a 90% score for Learnability, 90% for Efficiency, and 74% for Memorability. Overall, the average testing score is 85%, indicating that the developed UI/UX Design successfully achieves the goal of improving performance and user experience as intended.